2013
DOI: 10.2174/0929867311320060007
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent Agents: A Novel Concept and Preliminary Practice in Anti-HIV Drug Discovery

Abstract: The term multivalency (polyvalency) in the biological science is defined as the simultaneous binding of multiple ligands to one receptor (or multiple receptors to one ligand). The possibility of gaining potency and selectivity was significantly increased through the use of multivalent ligand as a homo- or hetero-dimer, thus multivalent ligands provided a more attractive strategy to design novel anti-HIV agents with therapeutic applications. Moreover, similar to phenomenon of multivalency, an alternative strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Both of the mentioned amino acids are crucial residues for forming favorable affinity with the ligand in previously reported binding modes. Besides, the multiple hydrogen bond interacted position in the binding mode shown in Figure c accorded with the second‐tolerated region we proposed earlier . We also implemented the molecular docking study of compound 5a with Z‐configuration, the result showed that (Z)‐5a revealed a similar clover‐like modality and generated a hydrogen bond with the backbone CO of Glu138; however, (E)‐5a seemed to fit better in the RT binding pocket than (Z)‐5a , so here we just presented the docking picture of (E)‐5a .…”
Section: Resultssupporting
confidence: 66%
“…Both of the mentioned amino acids are crucial residues for forming favorable affinity with the ligand in previously reported binding modes. Besides, the multiple hydrogen bond interacted position in the binding mode shown in Figure c accorded with the second‐tolerated region we proposed earlier . We also implemented the molecular docking study of compound 5a with Z‐configuration, the result showed that (Z)‐5a revealed a similar clover‐like modality and generated a hydrogen bond with the backbone CO of Glu138; however, (E)‐5a seemed to fit better in the RT binding pocket than (Z)‐5a , so here we just presented the docking picture of (E)‐5a .…”
Section: Resultssupporting
confidence: 66%
“…Unlike previous attempts to design poly/multi-valent drugs which were used in the development of anti-VRE(vancomycin resistant enterococci) antibiotics, multivalent influenza inhibitors, anti-HIV agents, antagonists of cholera toxin, and antitumor drugs we suggest an evolution guided design scheme (Song et al, 2013;Sun, 2007;Yuan et al, 2017;Zhang et al, 2002). Future studies in this direction should consider the negative design and screen the host cell proteome (for proteins with similar active site conformations) to avoid or minimize unintended interactions with host cellular proteins.…”
Section: Discussionmentioning
confidence: 99%
“…3 Therefore, there is still an urgent need for the identication of new anti-HIV drugs with new mechanisms of action to achieve HIV infection cure. 4,5 The HIV-1 capsid (CA) protein is essential for HIV-1 replication and plays crucial roles in both early (uncoating, reverse transcription, nuclear import, integration, etc.) and late (assembly and maturation) stages of the viral life cycle.…”
Section: Introductionmentioning
confidence: 99%
“…tert-Butyl (S)-(3-(3,5-diuorophenyl)-1-((4-methoxyphenyl) (methyl)amino)-1-oxopropan-2-yl)carbamate(5). A solution of (S)-2-((tert-butoxycarbonyl)amino)-3-(3,5-diuorophenyl)propanoic acid(4, 8.75 mmol, 2.7 g) in 15 mL dichloromethane was added PyBop (10.9 mmol, 5.7 g) at 0 C, and the mixture stirred for 0.5 h. Subsequently, DIEA (21.87 mmol, 3.61 mL) and 4-methoxy-N-methylaniline (7.29 mmol, 1.0 g) were added to the mixture and then stirred at room temperature for another 8-9 h (monitored by TLC).…”
mentioning
confidence: 99%